Comparison of Effects of Combined Physical Therapy Program and Exercise on Corrupted Balance Functions in Patient with Knee Bilateral Osteoarthritis - Ümit Dinçer,; Engin Çakar,; Baki Özdemir,; Mehmet Zeki Kıralp,; Hasan Dursun, (Archives of Rheumatology, 2008)
Objective: The aim of this study was to evaluate the effects of physical therapy and rehabilitation programs on corrupted balance function in patients with bilateral knee osteoarthritis and to determine any additional superior treatment other than quadricep and the hamstring muscle strengthening exercises. Patient and Methods: Forty patients aged between 59-84 years old, diagnosed with bilateral knee osteoarthritis according to American College of Rheumatology criteria participated in this study. Patients were randomized into two groups. The first group was applied 15 session physical therapy (therapeutic ultrasound and TENS) combined with exercise to both knees; the second group was given 15 session of only strengthening exercise to quadriceps and hamstring muscles. The patients were evaluated before and after two weeks treatment. WOMAC-total, WOMAC-pain and Berg Balance Scale were used to evaluate to disability and balance function. Results: In the inter-groups comparison after 15 session, there were statistically significant differences between two groups and the results of the first group was higher than those of second group in WOMAC-total, WOMAC-pain and Berg scale (p<0.05). There were statistically significant improvement in both groups in WOMAC-total, WOMAC-pain and Berg scale (p<0.05). Conclusion: According to this study we conclude that a physical therapy and rehabilitation program combined with exercise has more beneficial effects than only strengthening exercise program on balance restoration in bilateral knee osteoarthritis (Rheumatism 2008; 23: 9-13)